An intersectional pathway penalty: Filipina immigrant women inside and outside Canada's Live‐In Caregiver Program. (7th April 2021) - Lightman, Naomi; Banerjee, Rupa; Tungohan, Ethel; de Leon, Conely; Kelly, Philip
Abstract: This study uses Statistics Canada's Longitudinal Immigration Database to examine the 'intersectional pathway penalty' experienced by immigrant women from the Philippines entering Canada between 1996 and 2016 through three immigration categories. Estimating a series of growth curve models of employment income for 642, 885 women, we compare Filipina immigrants' earnings trajectories with female immigrants from other source countries to highlight how country of origin intersects with entry class to affect immigrant women's post‐migration labour market integration. Viewed through the lens of intersectionality, our results indicate that processes of differentiation tied to race and immigrant status result in Filipina women outperforming comparable women from other sources countries within the Live‐in Caregiver Program, where earnings are consistently lowest. However, within the higher earning Federal Skilled Worker Program entry class, Filipinas experience downward labour market mobility relative to women from other source countries, ultimately emphasizing the devalued nature of care work.